Exploring Slang Language in Different Songs Between Pop and Country Genres - Keren Febrian Mendrofa; Pasaribu, Arsen Nahum; Sembiring, Rony Arahta (English Lecturers and Teachers Association (ELTA), 2025)
This study examined slang in pop and country song lyrics from a sociolinguistic perspective, focusing on the types of slang and identifying the most dominant types in each genre. Song lyrics were obtained from internet transcripts, and a descriptive qualitative method was employed, based on the theory of Allan and Burridge (2006), which categorizes slang into five types, namely fresh and creative, flippant, imitative, acronym, and clipping. 341 slang words were identified, with 248 from the pop genre and 93 from the country genre. Clipping emerged as the most dominant type in both genres, accounting for 44.76% of slang in pop and 73.12% in country music. Other types followed in varying proportions: imitative (28.23% in pop, 9.68% in-country), flippant (15.74% in pop, 12.90% in-country), fresh and creative (10.08% in pop, 4.30% in-country), and acronym (1.21% in pop, and there is no single type of slang acronym in the country 0%). The findings indicate that slang usage is more prevalent in pop music, reflecting its tendency to use concise and accessible language to engage listeners. Keywords : Sociolinguistic, Slang, Song Lyrics, Pop and Country Genres